Research identity of university teachers in the city of Guayaquil - Asanza Moreira , José Manuel (Revista Universidad de Guayaquil, 2020)
Currently, it is necessary for universities to develop a well-defined digital identity, in relation totheir educational participation at the international level, however, not all people are predisposed tobe part of the digital interconnection that exists today, lagging behind of the rest of professionals.The purpose of thisresearch is to identify whether teachers at Guayaquil universities have a digitalidentity as researchers. The study was carried out with a quantitative approach, using a crosssectional deductive method, through exploratory research and with the survey as a measurementinstrument. As a result, there is evidence of the absence of the development of a digital identityand a researcher profile by teachers, therefore a teacher literacy process is needed focused onresearch and the use of digital tools that allows strengthening the investigative competences ofhigher education institutions, as they are key to the reputation of the institutions to which theybelong.
Keywords: Digital Identity; Scientific Reputation; Researcher Profile; , Scientific Communication